HEALTHY FOOD AS A FACTOR OF SERBIAN TOURISM COMPETITIVENESS - Đenadić Мiroljub (Economics of Agriculture, 2010)
Mass production of industrial goods enabled remarkable scientific and technological advances led to the threat of natural and living environment to the point that was brought into question the survival of plants and animals, and therefore the human species on the planet. In the last thirty years the world’s growing awareness of the need for sustainable development with the idea of meeting the needs of present generations without prejudice to the ability of future generations to meet similar needs. Sustainable tourism means tourism activity that performs its functions without any harmful impact on the environment, natural and social environment and unique culture. In recent decades the world has increased awareness of the importance of quality health foods that are entered into the human body from which the movement emerged, and later the production of organically grown food. Ideal basis for the positioning of Serbia as a tourist destination and increase its competitiveness are uncontaminated landscapes, clean air in rural areas, traditional hospitality of our village, the wealth of cultural and ethnographic content on our country and the food is prepared in a traditional-healthy way for centuries does not change with the inclusion organically grown food in the tourist industry.